Peningkatan Keandalan Jaringan Distribusi Dengan Rekonfigurasi - Puspita Dewi; Dian Yayan Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Reconfiguration of distribution network is one way to increase network reliability index of the distribution system. In this research, reliability index is computed using section technique. The optimization of the distribution network is achieved by changing the switches in the distribution network to obtain the most optimal distribution network configuration. The optimization method used in the genetic algorithm. The parameters that generated as a benchmark in determining the optimal distribution network is SAIFI (System Average Interruption Frequency index) and SAIDI (System Average Interruption Duration Index). The result from reconfigurated of the distribution network had a decrease of SAIFI value i.e 7.8199 % and the decrease of SAIDI value i.e 7.9968 % from before reconfiguration.Keywords : distribution network, genetic algorithm,reconfiguration, reliability,section technique